Analysis Catur Dimensional Strategic Da'wah (CDS) From A Sociological Perspective - Agung Drajat Sucipto (Jurnal Riksa Cendikia Nusantara, 2026)
Human beings do not live in a vacuum; they are born, grow, and interact within a complex social network known as society. It is this network with all its structures, rules, conflicts, and institutions that constitutes the primary field of study for the sociology of da'wah. This study employs a literature review method with a qualitative approach to establish a conceptual foundation and develop both theoretical and practical aspect. Within the CDS framework, this analysis of social interaction deepens the Psycho-Sociological Dimension by incorporating the lens of interactionist sociology. Sociologically, social movements typically emerge from dissatisfaction with the status quo and are mobilized through three key components: an interpretive framework (framing), a resource mobilization structure, and political opportunity. Da’wah effectively provides all three of these components. First, da’wah offers a robust